Crown gall of grapevine and prospects for its biological control - L. Konup; M. Pikovskyi; M. Riabyi; A. Konup; M. Kyryk (Рослинництво та ґрунтознавство, 2024)
The relevance of this study is conditioned by the spread of bacterial diseases of grapes in the south of Ukraine and the necessity of improving methods of pathogen identification and protection. The purpose of this study was to establish the area of bacterial grape cancer in Odesa region and to develop preventive measures based on the biological method. The study involved the inspection of industrial plantations for symptoms of the disease and its spread in the field. The molecular biological method of real-time polymerase chain reaction (PCR) was employed to identify the crown gall pathogen. The study was conducted following a certified methodology. PCR laboratory equipment was used to identify phytopathogens. As a result of the phytosanitary inspection of grape plantations of various farms in Odesa region, the study found grape bushes with characteristic symptoms of crown gall, with tumorous tissue growths in various parts of the plants: on the branches, stem, and grafting sites. Overall, grape crown gall is characterised by a wide distribution in the study area. According to the findings of the phytosanitary survey, the spread of bacterial grape cancer on different varieties ranged between 0.3-35%. The causative agent of the disease, A. tumefaciens, was identified in real time by PCR. The disease manifested itself in the form of characteristic symptoms and developed in a latent form. The developed multiplex PCR allowed for the simultaneous analysis of multiple strains of pathogenic agrobacterial isolates. Two isolates of agrobacteria were identified among the majority of isolates that were subsequently tested for tumour suppression: ILVM1 and ILVM2, which had elevated levels of antagonistic properties against the crown gall pathogen. The pathogenicity of the isolated agrobacteria on test plants of tomato and sunflower confirmed the findings of these properties obtained in vitro. The isolates of ILVM1 and ILVM2 agrobacteria considerably inhibited the growth of tumours on the stems of test plants compared to the pathogenic strain, and therefore they can be used in the future against the crown gall pathogen and to protect grape plants from secondary infection by the pathogen from the soil. The findings can be used to improve methods of biological plant protection against bacterial infections